B. Perform the indicated operations. Simplify your answer​

B Perform The Indicated Operations Simplify Your Answer class=

Sagot :

Perform the indicated operations. Simplify your answer!

1. 2ab ( 4a² + 3ab - 7b²) = 8a³b + 6a²b² - 14ab³

2. -3xy (x³y³ - 3x²y + 7xy²) = -3x⁴y⁴ + 9x³y² - 21x²y³

3. (x + 2)(x² - 3x + 2) = x³ - x² - 4x + 4

4. (2x - 1)(2x² + 4x + 3) = 4x³ + 6x² + 2x - 3

5. (12y² - 9y + 16) (8y³ - 14y + 5) = 96y⁵ - 72y⁴ - 40y³ + 186y² - 269y + 80

6. (25a⁵b³c) ÷ (5ab⁴c) = 5a⁴b⁻¹

7. (16a³b²c⁵ - 24a⁵bc⁴ + 44a⁷b⁶c⁶) ÷ (4a²bc³) = ac(4bc - 6a² + 11a⁴b⁵c²)

8. (30c² + 19ac - 63a²) ÷ (6c - 7a) = 5c + 9a

9. (a⁶ + b⁶) + (a² + b²) = a²(a⁴ + 1) + b²(b⁴ + 1)

10. (6w³ + 7w² - 12w + 15) ÷ (2w² + 3w - 5) = (3w - 1) +  [tex]\frac{6w + 10}{2w^2 + 3w - 5}[/tex]

Step-by-step explanation:

Given:

1. 2ab ( 4a² + 3ab - 7b²)

2. -3xy (x³y³ - 3x²y + 7xy²)

3. (x + 2)(x² - 3x + 2)

4. (2x - 1)(2x² + 4x + 3)

5. (12y² - 9y + 16) (8y³ - 14y + 5)

6. (25a⁵b³c) ÷ (5ab⁴c)

7. (16a³b²c⁵ - 24a⁵bc⁴ + 44a⁷b⁶c⁶) ÷ (4a²bc³)

8. (30c² + 19ac - 63a²) ÷ (6c - 7a)

9. (a⁶ + b⁶) + (a² + b²)

10. (6w³ + 7w² - 12w + 15) ÷ (2w² + 3w - 5)

Question:

Perform the indicated operations. Simplify your answer!

Solutions:

1. 2ab ( 4a² + 3ab - 7b²)

= 8a³b + 6a²b² - 14ab³

2. -3xy (x³y³ - 3x²y + 7xy²)

= -3x⁴y⁴ + 9x³y² - 21x²y³

3. (x + 2)(x² - 3x + 2)

= x³ - 3x² + 2x + 2x² - 6x + 4

= x³ - x² - 4x + 4

4. (2x - 1)(2x² + 4x + 3)

= 4x³ + 8x² + 6x - 2x² - 4x - 3

= 4x³ + 6x² + 2x - 3

5. (12y² - 9y + 16) (8y³ - 14y + 5)

= 96y⁵ - 168y³ + 60y² - 72y⁴ + 126y² - 45y + 128y³ - 224y + 80

= 96y⁵ - 72y⁴ - 40y³ + 186y² - 269y + 80

6. (25a⁵b³c) ÷ (5ab⁴c)

= 5a⁴b⁻¹

7. (16a³b²c⁵ - 24a⁵bc⁴ + 44a⁷b⁶c⁶) ÷ (4a²bc³)

= (16a³b²c⁵) ÷ (4a²bc³) - (24a⁵bc⁴) ÷ (4a²bc³) + (44a⁷b⁶c⁶) ÷ (4a²bc³)

= 4abc² - 6a³c + 11a⁵b⁵c³

= ac(4bc - 6a² + 11a⁴b⁵c²)

8. (30c² + 19ac - 63a²) ÷ (6c - 7a)

= (6c - 7a)(5c + 9a) ÷ (6c - 7a)

= 5c + 9a

9. (a⁶ + b⁶) + (a² + b²)

= a⁶ + b⁶ + a² + b²

= a⁶ + a² + b⁶ + b²

= a²(a⁴ + 1) + b²(b⁴ + 1)

10. (6w³ + 7w² - 12w + 15) ÷ (2w² + 3w - 5)

= (3w - 1)(2w² + 3w - 5) ÷ (2w² + 3w - 5) +  [tex]\frac{6w + 10}{2w^2 + 3w - 5}[/tex]

= (3w - 1) +  [tex]\frac{6w + 10}{2w^2 + 3w - 5}[/tex]

Learn more about

  • Theory about Perform the indicated operation, then simplify​: https://brainly.ph/question/6905770

#SPJ1